2019
DOI: 10.1371/journal.pone.0223212
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interaction between the ZPBP2-ORMDL3/Zpbp2-Ormdl3 region and the circadian clock

Abstract: Genome-wide association study (GWAS) loci for several immunity-mediated diseases (early onset asthma, inflammatory bowel disease (IBD), primary biliary cholangitis, and rheumatoid arthritis) map to chromosomal region 17q12-q21. The predominant view is that association between 17q12-q21 alleles and increased risk of developing asthma or IBD is due to regulatory variants. ORM sphingolipid biosynthesis regulator (ORMDL3) residing in this region is the most promising gene candidate for explaining association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In this region, we found that the WAS-induced Zpbp2-Ormdl3 chromatin loop replaced the Ikzf3-Ormdl3 and Ormdl3-Nr1d1 super-enhancer loops in control at the chromatin looping sites that include the GR bound Ikzf3 - Zpbp2 bidirectional promoter and Nr1d1 super-enhancer. 22 , 35 In addition, WAS elevated Nr1d1 super-enhancer GR binding ( Figure 4 B). This pattern correlates with IBS and IBD SNP rs2872507 regulates transcription of this region and IBD SNP (rs12936231) mediated long-range regulation of NR1D1 via the formation of IBD-related ZPBP2-ORMDL3 loop ( Figures 4 C and 4D).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In this region, we found that the WAS-induced Zpbp2-Ormdl3 chromatin loop replaced the Ikzf3-Ormdl3 and Ormdl3-Nr1d1 super-enhancer loops in control at the chromatin looping sites that include the GR bound Ikzf3 - Zpbp2 bidirectional promoter and Nr1d1 super-enhancer. 22 , 35 In addition, WAS elevated Nr1d1 super-enhancer GR binding ( Figure 4 B). This pattern correlates with IBS and IBD SNP rs2872507 regulates transcription of this region and IBD SNP (rs12936231) mediated long-range regulation of NR1D1 via the formation of IBD-related ZPBP2-ORMDL3 loop ( Figures 4 C and 4D).…”
Section: Resultsmentioning
confidence: 91%
“…In addition to IBS and IBD-related DEGs encoded within the conserved Nr1d1-Ormdl3-Ikzf3-Grb7-Erbb2-Stard3-Fbxl20 chromatin , we observed stress responses in the validated circadian chromatin 3D structure-regulated genes Nr1d2 , Npas2 , Rorc , and Pard3 . 8 , 21 , 22 , 31 , 35 , 41 , 42 NR1D1 downstream circadian gene Arntl ( Bmal1 ), Nfil3 elevated. 16 IBS therapeutic target homolog Slc9a3 (hydrogen exchanger 3 /Nhe3 ) decreased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations